Coexistence of resistance oscillations and the anomalous metal phase in a lithium intercalated TiSe2 superconductor - Menghan Liao (Nature Portfolio, 2021)
The interplay between superconductivity and charge density wave (CDW) gives rise to exotic quantum phenomena. Here, the authors observe magnetoresistance oscillations and an anomalous metal state due to the coexistence of superconductivity and CDW in lithium intercalated TiSe2.